DETERMINASI RETURN SAHAM MELALUI ARUS KAS, PROFITABILITAS, DAN PERPUTARAN PERSEDIAAN PADA PT DHARMA SATYA NUSANTARA Tbk PERIODE 2015-2024 - Dwi Ismawati; Prama Indra Ishwara (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This study aims to determine and analyze the extent of the influence of Operating Cash Flow, Net Profit Margin, and Inventory Turnover on Stock Returns atPT Dharma Satya Nusantara Tbk for the period 2015-2024. The method used in this study is quantitative, employing financial statement data. The analytical method applied include descriptive tests, classical assumption tests, linear regression analysis, hypothesis testing. The results of the study indicate that Operating Cash Flow has no significant effect (t-count -0.925<t-table 2.447) with a significance of (0.391>0.05). The test results from Net Profit Margin has no significance effect (t-count 0.464<t-tabel 2.447) with a significance of (0.659>0.05). The test result for Inventory Turnover has no significance effect (t-count 1.245<t-tabel 2.447) with a significance of (0.260>0.05). Simultaneously, Operating Cash Flow, Net Profit Margin, Inventoy Turnover on Stock Returns (f-count 0.628<f-table 4.5757 with a significance (0.623>0.05).